(untitled) (Nepalese Journal of Ophthalmology, 2020)
Introduction: The impact of Meibomian gland dysfunction (MGD) on the overall health of the patient is not known. Efforts are being made to understand the association of dyslipidemia with MGD. The objective of the study was to determine the association of dyslipidemia with the severity of MGD, a contributor to dry eye syndrome. Materials and methods: We performed an observational case-control study at a tertiary care centre over 18 months and enrolled 116 patients in the age group of 18 to 65 years. A detailed history and clinical examination were done. Following examination, patients were allocated into two groups, patients with MGD and no history of dyslipidemia (cases) and patients without MGD and no history of dyslipidemia (controls). A fasting lipid profile was done for both these groups. The data were subsequently analyzed with SPSS software. Results: Fifty six (48.3%) of the participants had serum total cholesterol levels ≥200 mg/dl, with a significant association between higher cholesterol levels and severity of MGD (p=0.0001). 77 (66.4%) of the participants had serum triglycerides levels of ≥150 mg/ dl. There was a significant association between the severity of MGD and elevated triglyceride levels (95% confidence interval of Pearson’s chi-square 28.16, p=0.0001). A significant association was also observed between the severity of MGD and elevated LDL levels (95% confidence interval of Pearson’s chi-square 5.95, p=0.015). However, no association was found between HDL levels and the severity of MGD. Conclusion: The results suggest that patients with MGD and without any history of dyslipidemia, may have higher blood levels of lipid profile components as compared to age-matched controls.